2006
DOI: 10.1183/09031936.06.00150705
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive ventilation for prevention of post-extubation respiratory failure in obese patients

Abstract: Current recommendations for management of obese patients post-extubation are based on clinical experience and expert opinions. It was hypothesised that the application of noninvasive ventilation (NIV) during the first 48 h after extubation in severely obese patients would reduce post-extubation failure and avert the need for reintubation.Following protocol-driven weaning trials, 62 consecutive severely obese patients (body mass index o35 kg?m -2 ) were assigned to NIV via nasal mask immediately post-extubation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0
18

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(91 citation statements)
references
References 27 publications
1
66
0
18
Order By: Relevance
“…NPPV has also been successfully used for the prevention of ARF in the first 48 h post-extubation in severely obese patients [89]. These data support the use of NPPV as a means of prevention of ARF in patients at high risk of extubation failure, in selected patients and in appropriate settings allowing for strict monitoring and prompt ETI.…”
Section: Post-extubation Respiratory Failurementioning
confidence: 53%
“…NPPV has also been successfully used for the prevention of ARF in the first 48 h post-extubation in severely obese patients [89]. These data support the use of NPPV as a means of prevention of ARF in patients at high risk of extubation failure, in selected patients and in appropriate settings allowing for strict monitoring and prompt ETI.…”
Section: Post-extubation Respiratory Failurementioning
confidence: 53%
“…The results from this study confirm again that the use of NIV immediately after extubation results in decreased incidence of respiratory failure after extubation and improved survival. The benefits of NIV in the prevention of respiratory failure after extubation were also documented in severely obese patients in a casecontrol study (79). In this study, the benefits in survival were also restricted in hypercapnic patients only.…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 57%
“…NIV in selected chronic hypercapnic patients if applied within the first 48 hours post-extubation following established weaning protocols reduces hospital mortality. There was also a significant reduction of length of ICU and hospital stay [33]. This study has shown that the use of NIV in the first 48 hours post-extubation might be effective in avoiding respiratory failure.…”
Section: Niv As Weaning Strategymentioning
confidence: 66%
“…Only few studies address the problem of weaning in critically obese patients [32][33][34]. Currently, the management of these patients is based on clinical experience and expert opinions [33].…”
Section: Niv As Weaning Strategymentioning
confidence: 99%
See 1 more Smart Citation